(3GddHGH Yf Ydhe GdcJGHs - (3YeQ Hf Ydj Hf YGOd GdMfHdj GdOeTbqj, CHh MaU, SQGL GdOjf , HYO (B880 (3g` s ((3GdbSWfWjfjIs)
(3BNQgG (B:s
(3cJHJ HQSe (B: (3YHO GdQMef CafOj Gdehdi HGdaSWfWjfjI , fLd Gdehdi MSGe GdOjf CafOjs
(3eUOQ GbJfGA GdCUd (B:s
(3aGVd CMeOs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs